KESESUAIAN PERMENKOMINFO NOMOR 05 TAHUN 2020 DENGAN PRINSIP KEBEBASAN BERPENDAPAT DAN BEREKSPRESI DALAM HAK ASASI MANUSIA - Ridho Dwi Rahardjo; Wiwik Afifah (Gapenas Publisher, 2022)
The current government can block Electronic System Operators through Regulation of the Minister of Communication and Information Number 5 of 2020 concerning Private Scope Electronic System Operators. However, this regulation does not regulate in detail. This study aims to find things that must be done whether they are in line with the principles of freedom and expression. By going through a normative approach method with the aim of answering issues based on the scientific side. The results of this study indicate that Permenkominfo No. 5 of 2020 is not in accordance with the principle of freedom of opinion and expression because the regulation related to the phrase